2019
DOI: 10.3389/fimmu.2019.00649
|View full text |Cite
|
Sign up to set email alerts
|

Commensal and Pathogenic Bacteria Indirectly Induce IL-22 but Not IFNγ Production From Human Colonic ILC3s via Multiple Mechanisms

Abstract: Innate lymphoid cells (ILCs) are a diverse family of cells that play critical roles in mucosal immunity. One subset of the ILC family, Group 3 ILCs (ILC3s), has been shown to aid in gut homeostasis through the production of IL-22. IL-22 promotes gut homeostasis through its functional effect on the epithelial barrier. When gut epithelial barrier integrity is compromised, such as in Human Immunodeficiency Virus (HIV) infection and inflammatory bowel disease (IBD), microbes from the gut lumen translocate into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…These cells start to secrete IL-22 after stimulation with enteric commensals. 60 It is subject of further studies to disclose which IL-22-producing cell type is affected by A. finegoldii .…”
Section: Discussionmentioning
confidence: 99%
“…These cells start to secrete IL-22 after stimulation with enteric commensals. 60 It is subject of further studies to disclose which IL-22-producing cell type is affected by A. finegoldii .…”
Section: Discussionmentioning
confidence: 99%
“…46 Here, two of the Gram-negative commensals tested (P. stercorea and A. junii) reside within genera of bacteria that are reported to contain pathobionts, 47,48 and thus members of these genera may induce inflammation in the setting of epithelial barrier damage. Interestingly, we have previously shown that these exact species can also induce IL-22 production by human colonic ILC3s, 49 which is a cytokine with a role in epithelial barrier maintenance and regulation of intestinal health. However, it is important to note that while we did investigate the effect of four commensal bacteria representing four different phyla on the induction of cytokine production by Group 1 ILCs, we acknowledge that there are a multitude of different bacterial species in the human gut and therefore we cannot conclude that all bacteria would elicit similar responses in Group 1 ILCs.…”
Section: Discussionmentioning
confidence: 99%
“…A release was signed by all patients undergoing surgery to allow unrestricted use of discarded tissue. LPMCs were isolated from tissue samples as previously described 49,55,56 and stored in liquid nitrogen until use.…”
Section: Lamina Propria Mononuclear Cells (Lpmc)mentioning
confidence: 99%
“…On the one hand, Castleman and colleagues showed that both Gram-positive and -negative commensal bacteria induced the expression of IL-22 by ILC3s. This IL-22 production by ILC3s was not mediated through direct recognition of bacteria, but rather mediated indirectly by myeloid dendritic cells (mDCs) and is partly dependent on IL-23 and IL-1β [ 39 ]. On the other hand, another report showed that Bacillus anthracis can downregulate IL-22 in ILC3s via an IL-23 mediated MAPK signaling pathway [ 40 ].…”
Section: Il-22 In the Gastrointestinal Tractmentioning
confidence: 99%